2000
DOI: 10.1186/bf03549638
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas Isolated from the Respiratory Tract of Cattle and Goats in Tanzania

Abstract: Kusiluka LJM, Ojeniyi B, Friis NF, Kazwala RR, Kokotovic B: Mycoplasmas isolated from the respiratory tract of cattle and goats in Tanzania. Acta vet. scand. 2000,41,299-309. -A microbiological study ofthe mycoplasma flora in the respiratory tracts of cattle and goats in selected regions of Tanzania is described. In the examination of cattle, mycoplasmas were isolated from 60 (17.8%) of the 338 examined lung samples, 8 (47.1%) of the 17 lymph nodes, 4 (13.3%) of the 30 pleural fluid samples and 4 (3.9%) ofth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…capripneumoniae (Mccp), Mmc, and Movi. [1][2][3]. Among these, Mccp mainly infect ungulates including sheep, goats, and wild animals [4][5][6], and it is associated with 60% mortality and 90% morbidity in goats [7].…”
Section: Introductionmentioning
confidence: 99%
“…capripneumoniae (Mccp), Mmc, and Movi. [1][2][3]. Among these, Mccp mainly infect ungulates including sheep, goats, and wild animals [4][5][6], and it is associated with 60% mortality and 90% morbidity in goats [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Ethiopia prevalence of CCPP in female animals (6.66%) was found lowered compared to bucks 24.08%(Regassa et al, 2010). Various other researchers from Ethiopia and Tanzania reported that sex does not play signi cant role in epidemiology of CCPP(Kusiluka et al, 2000;Hadush et al, 2009;Mekuria et al, 2010; Yousuf et al, 2012…”
mentioning
confidence: 97%